Development of Rukhsah Learning Application Based on SAC (Smart Apps Creator) to Improve Students' Argumentation Skills - Izzati, Leni Nurul; Fadly, Wirawan (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2025)
The development of the SAC (Smart Apps Creator) based Rukhsah learning application aims to improve students' argumentation skills, as well as make a real contribution to learning innovation in the digital era. This study uses the Research and Development (R&D) Method by referring to the ADDIE research model, namely Analysis, Design, Development, Implementation, and Evaluation. This study aims to determine the validation, practicality, and effectiveness of the use of the Rukhsah Application. This research was conducted at MTs Muhammadiyah 2 Jenangan Ponorogo. The number of research samples was 36 students taken through random sampling techniques. Data were obtained from questionnaires, and argumentation skills tests were analyzed using quantitative descriptive and qualitative descriptive to determine practicality, and statistical tests Sample Paired T Test and Choen's d to determine the level of effectiveness of the developed application. The results of the study show that the Rukhsah Application has a validation rate of 92% in the very valid category and a practicality level of 86% in the very practical category. The effectiveness in improving students' argumentation skills obtained a Cohen's d score of 5.541, which is >0.8 in the large effect category.